"Maltrato intrafamiliar y rendimiento académico en escolares de la Institución Educativa Miguel Grau Seminario, 2011" - Quintana Martinez, Cinthya Paola (2011)
This research study is a descriptive - correlational was conducted in the school education institution Miguel Grau Seminario of Salaverry, whit the main of dertermine the relation between the domestic abuse and academic performance in school. The sample consisted of 68 students selected based on inclusion criteria. The data collection was obtained by applying two – denominated instruments: Presence identification scale or non domestic abuse and Tab for determine the level of academic performance. The data were tabulated and presented in statistical tables of single and double entry. The analysis statistical was performed by applying test, the test of independence of criteria or Chi square. After the analysis reached the following conclusions: Of total school; the 41.2 percent of students presented domestic abuse mild, the 39.7 percent didn´t shown domestic abuse, the 19.1 percent shown domestic abuse moderate and nobody presented serious domestic abuse. The 44.1 percent shown a good academic performance, the 38.2 percent shown a regular academic performance, the 8.8 percent shown low academic performance and the other 8.8 percent shown the best academic performance. Highly significant statistical relationship exists between domestic abuse and academic performance.